2016
DOI: 10.1161/circheartfailure.115.002897
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Proteinuria and Reduced Glomerular Filtration Rate Predicts Renal Replacement Therapy in Patients Supported With Continuous-Flow Left Ventricular Assist Devices

Abstract: Background— Renal failure requiring renal replacement therapy (RRT) has detrimental effects on quality of life and survival of patients with continuous-flow left ventricular assist devices (CF-LVADs). Current guidelines do not offer a decision-making algorithm for CF-LVAD candidates with poor baseline renal function. Objective of this study was to identify risk factors associated with RRT after CF-LVAD implantation. Methods and Results— T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Kirklin et al [20] reported that increased preoperative renal dysfunction, quantified by blood urea nitrogen and estimated glomerular filtration rate, was associated with increased postoperative mortality, particularly in the first 3 months. We also found, similar to Chertow et al [28], that preoperative serum creatinine was higher in those who developed moderate AKI ( p = 0.045), which subsequently increased the risk of mortality, consistent with the previous literature [20, 25]. This increased preoperative creatinine may be an indicator of baseline renal dysfunction of some degree, though various biomarkers and ratios (such as urine albumin and the urine albumin creatinine ratio) may prove more reliable [28, 29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Kirklin et al [20] reported that increased preoperative renal dysfunction, quantified by blood urea nitrogen and estimated glomerular filtration rate, was associated with increased postoperative mortality, particularly in the first 3 months. We also found, similar to Chertow et al [28], that preoperative serum creatinine was higher in those who developed moderate AKI ( p = 0.045), which subsequently increased the risk of mortality, consistent with the previous literature [20, 25]. This increased preoperative creatinine may be an indicator of baseline renal dysfunction of some degree, though various biomarkers and ratios (such as urine albumin and the urine albumin creatinine ratio) may prove more reliable [28, 29].…”
Section: Discussionsupporting
confidence: 93%
“…Identifying biomarkers that confirm cardiac surgery-associated AKI, such as urine neutrophil gelatinase-associated lipocalin, have been evaluated, but to date the results have been unreliable in predicting clinical outcomes [24]. Recently, preoperative estimated glomerular filtration rate and proteinuria were identified as predictors of postoperative renal dysfunction necessitating renal replacement therapy in continuous-flow LVAD recipients [25]. Recent evidence from a single center showed intravenous inotropic therapy to be noninferior to LVAD placement for end-stage heart failure patients with respect to mortality and the need for renal perfusion [26].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postimplantation AKI is 7%-14% in continuous-ow devices [29]. In addition, RRT is needed in a subset of patients who develop post-LVAD AKI [30].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney failure after left ventricular assist device (LVAD) is an uncommon occurrence 95 . This may be because LVAD therapy is contraindicated in patients at high risk for kidney failure, as it is known that LVAD patients who require dialysis have extremely high mortality (>60%) 96 . In LVAD recipients who develop kidney failure, both PD and hemodialysis can be considered as treatment modalities, although specific management of LVAD patients on dialysis is complex and beyond the scope of this review.…”
Section: Lvadsmentioning
confidence: 99%